The effects of psychiatric treatment on depression, anxiety, quality of life, and sexual dysfunction in patients with inflammatory bowel disease - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2016)
Objective: Depression and anxiety are common disorders in inflammatory bowel disease (IBD). Our aim is to prospectively determine the effect of psychiatric treatment on scores for depression, anxiety, quality of life (QoL), and sexual dysfunction in an outpatient population diagnosed with IBD and also anxiety and/or depression disorder. Patients and methods: Patients who scored higher than the cutoff point on the Hospital Anxiety Depression Scale were referred for further structured psychiatric evaluation and determination of the need for psychiatric drug treatment. Patients who underwent drug therapy completed Short Form-36 (SF-36) and the Arizona Sexual Experience Scale at baseline and after 6 months of follow-up. Results: Major depressive disorder and generalized anxiety disorder were the most common diagnoses. After 6 months, 47 patients had completely adhered to drug treatment (group A), whereas 20 were nonadherent (group B). In group A, all domains of SF-36, Arizona Sexual Experience Scale, depression/anxiety scores, and Crohn's disease activity index were statistically improved after treatment when compared with the baseline. In group B, the three domains of SF-36, platelet count, and mean corpuscular volume were worse between baseline and at 6 months. Conclusion: In IBD patients having any psychiatric disorder, 6 months of antidepressant drug treatment is associated with an improvement in depression, anxiety, QoL, and sexual functioning scores, as well as an improvement in Crohn's disease activity index. On the other hand, insufficient psychiatric treatment seems to be related to a poor QoL.
Keywords: anxiety; depression; sexual dysfunction; psychiatric treatment; inflammatory bowel disease; PATIENTS PERCEPTIONS; ULCERATIVE-COLITIS; ATTACHMENT; ANTIDEPRESSANTS; COMORBIDITY; RELIABILITY; EXPERIENCES; SYMPTOMS; RELAPSE; IMPACT